Understanding modelled sea-air CO2 flux biases in the Southern Ocean through the seasonal cycle - Mongwe, Ndunisani Precious (University of Cape Town, 2019)
The Southern Ocean forms a vital component of the earth system as a sink of CO2 and heat, taking over 40% of the annual oceanic CO2 uptake (75% of global heat uptake), slowing down the accumulation of CO2 in the atmosphere and thus the rate of climate change. However, recent studies based on the Coupled Model Intercomparison Project version 5 (CMIP5) Earth System Models (ESMs) show that CMIP5 ESMs disagree on the phasing of the seasonal cycle of the CO2 flux (FCO2) and compare poorly with available observation estimates in the Southern Ocean. Notwithstanding these differences, the seasonal cycle is a dominant mode of CO2 variability in the Southern Ocean, and hence this is an important bias. Previous studies suggest that these biases of FCO2 in ESMs might be a significant limitation to the long-term simulation of CO2 characteristics in the Southern Ocean. Consequently, this study has three primary objectives: first, to develop a process-based diagnostic method to analyze and isolate key biases and their underlaying mechanisms in the model-observations seasonal cycle of FCO2 differences for forced ocean models and ESMs. Second, to use this framework to examine sources of biases responsible for the limited skill of CMIP5 models in simulating the seasonal cycle of FCO2 with respect to observed estimates. Thirdly, to investigate how these present-day biases in the seasonality and drivers of CO2 in CMIP5 ESMs affect modelled longterm changes in the mechanisms of CO2 uptake in the Southern Ocean. In the first part of the dissertation, an objective diagnostic framework was established to analyze model-observation biases in the seasonal scale of FCO2 using the NEMO PISCES ORCA2LP model output, and Takahashi et al. (2009) observed estimates. The diagnostic framework focuses on examining the relative contributions of the competing drivers (SST and DIC) and related processes (solubility, biological and mixing) to instantaneous monthly changes in surface pCO2 (and FCO2) at the seasonal scale. In the second part of the dissertation, this approach is applied to 10 CMIP5 models in the Southern Ocean, to investigate the mechanistic basis for the seasonal cycle of FCO2 biases. It was found that FCO2 biases in CMIP5 models can be grouped into two main categories, i.e. group-SST and group-DIC. Group-SST models are characterized by an exaggeration of the seasonal rates of change of Sea Surface Temperature (SST) in autumn and spring during the cooling and warming peaks, respectively. These faster-than-observed rates of change of SST tip the control of the seasonal cycle of pCO2 and FCO2 towards SST and result in divergence between the observed and modelled seasonal cycles, particularly in the Sub-Antarctic Zone. While almost all analyzed models show these SST-driven biases, 3 out of 10 (namely NorESM1-ME, HadGEM2-ES and MPI-ESM, collectively the group-DIC models) compensate the solubility bias because of their exaggerated primary production, such that biologically-driven DIC changes become the regulators of the seasonal cycle of FCO2. It was also found that despite significant differences in the spatial characteristics of the mean annual fluxes, CMIP5 models show a zonal homogeneity in the seasonal cycle of FCO2 at the basin-scale in contrast to observed estimates. In the final third of the dissertation, using five CMIP5 ESMs from the RCP8.5 scenario, it was found that CMIP5 models present climate biases in the seasonality and drivers of FCO2 are fundamental to how models simulate long-term changes in the mechanisms of CO2 uptake in the Southern Ocean. Although all five analyzed models show an increased annual mean CO2 uptake by the end of the century, they show significant differences in the mechanisms. The present-day temperature biased models (group-SST) generally maintain the dominance of the temperature driver in the seasonal variability of FCO2 to end of the century. But show enhanced CO2 uptake due to increased anthropogenic atmospheric CO2 and decreased surface CO2 buffering capacity but they display a weak to null role of biological activity in the increased CO2 sink. On the other hand, the increased CO2 uptake at the end of the century in group-DIC models is explained increased biological driven CO2 uptake in spring, linked to increased Revelle factor and solubility driven CO2 uptake in winter. Increased Revelle factor at the end of the century enhance pCO2 changes for even smaller DIC changes.